PENGARUH PENGAWASAN TERHADAP KEBERHASILAN PROGRAM DANA DESA DENGAN GOOD GOVERNANCE SEBAGAI VARIABEL INTERVENING (Studi Kasus Di Kecamatan Bancak Kabupaten Semarang Jawa Tengah) - Pandi Afandi (Among Makarti, STIE AMA Salatiga, 2019)
Abstract Observation represent the important variable in ascertaining what planning have been executed, with the observation of hence will have an in with to arrange the good governance which is on finally support the its reached program efficacy. Just as in fund management of countryside 9 village in District of Bancak of Sub-Province of Semarang of Central Java in supporting efficacy and its village progress. Intention of this research is to know the influence of variable observation to arranging good governance, influence of good governance to efficacy program of village fund, and both influence of the variable to efficacy of program of village fund, and also what good governance become the variable intervening for the relation of observation with the efficacy of program of village fund. Its result indicate that the observation have an effect on positive significant to good governance and good governance have an effect on positive signifikan to efficacy of program of village fund, but observation have an effect on the negative significant to efficacy of program of village fund and also good governance become the connective variable intervening of variable observation with the efficacy of program of villagec fund.Increase of active role lead the village and BPD in observing the way execution of program of village fund., process the observation of execution of program of village fund having the character of more persuasive. ( persuasive control) and active participation of village society represent the matter suggested from this research result. Keywords: Observation, Good Governance and Efficacy of village fund program